Criptosporidiosis en niños de Costa Rica: Estudio transveral y longitudinal - Mata, Leonardo (1984)
The present report is a systematic study of children, with and without diarrhea from Costa Rican metropolitan areas and southern rural higlands. Children were observed, respectively, at emergencies, Hospital Nacional de Niños, and in a field station in Puriscal; urban children were studied vertically, rural children were observed prospectively (cohort study). Cryptosporidium sp. was found in 4.3% of the cases of diarrhea; diahrrea was generally severe in urban children, but mild in the rural. Infection was detected in urban children less than one year of age: contrasting, no rural infants were found infected, which might be related to breast-feeding, since Puriscal infants were intensively breast-fed for several months, while many urban infants were not breast-fed or were weaned earlier. Cryptosporidium sp. appeared during the warm, rainy and humid months of May through August, when the coccidium was associated with 14.8% of the urban and 15.4% of the rural diarrheas. AH urban cases presented dehydration which was corrected with oral rehydration salt therapy, and occasionally with intravenous fluids; dehydration was not common in the rural cases.